Assessing the Impact of the 2023 Türkiye–Syria Earthquake on Sleep Disturbances among Children and Adolescents - Rahaf Akel Rajjoub; Anna Mohieldeen Ahmad; Emad Ghassan Eshak; Abeer Saleem Assaf; I Gede Juanamasta; Abdulkareem Iblasi; Laila Adnan Assaf (Jurnal Keperawatan Soedirman, 2026)
Despite growing evidence that disasters adversely affect children's sleep, data on displaced Syrian children following the 6 February 2023 Türkiye–Syria earthquake remain scarce. This study investigated the prevalence and determinants of sleep disturbances among displaced Syrian children and adolescents one month after the earthquake. A cross-sectional study was conducted from March to April 2023 among 150 participants aged 7–17 years residing in five government shelters in Syria. Sleep disturbances were assessed using the Child and Adolescent Sleep Checklist (CASC), and data were analyzed using independent-samples t-tests, one-way analysis of variance, and Pearson correlation. Clinically significant sleep disturbance (CASC ≥18) was identified in 95.3% of participants. Irregular nocturnal sleep affected nearly all participants, while 44.7% experienced insufficient sleep. Children aged 7–12 years had significantly higher scores for sleep breathing/unstable sleep and parasomnia/sleep movement than adolescents (both p ≤ 0.001). Educational grade was associated with multiple sleep domains, whereas longer nocturnal sleep duration was associated with lower sleep disturbance scores (both p < 0.05). These findings reveal a substantial burden of sleep disturbance among displaced children following a major disaster and support integrating age-specific sleep assessment and targeted interventions into post-disaster pediatric care.